Hegel's theory of modern bureaucracy - Shaw, Carl K.Y
According to the author there are three contentions, First Hegel's theory of bureaucracy is as comprehensive as Weber's ideal type of bureaucratic organization. He argues that this by making a sociological reformulation of Hegel's model and comparing it with the Weberian paradigm. Second, Hegel adapts the Aristotelian category of practical judgement in characterising the bureaucratic activity as subsumption. This characterization is contrary to the dominant view that bureaucracy embodies more instrumental rationality and salves some difficulties in Hegel's political thought. Third, Hegel's conceptualization can contribute to a liberal theory of bureaucracy that apprehends modern political reality more adequ
Keywords: Weber, Max; Hegel, George W.F.; Bureaucracy